Analysis of the Impact of Stakeholder Engagement, Social Business Model, and Financial Sustainability on the Growth of Social Entrepreneurs - Judijanto, Loso; Purwanti, Ari; Wijayanti, Indah Oktari (West Science Journal Economic and Entrepreneurship, 2024)
This study investigates the influence of stakeholder engagement, social business models, and financial sustainability on the growth of social entrepreneurs. Employing a quantitative approach, data were collected from 230 social entrepreneurs and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results indicate that all three factors—stakeholder engagement, social business models, and financial sustainability—significantly and positively impact the growth of social entrepreneurs. Among these, stakeholder engagement emerged as the most influential factor, followed by social business models and financial sustainability. The findings underscore the critical role of strong stakeholder relationships, innovative business models, and financial stability in fostering the growth and scalability of social enterprises. These insights provide valuable guidance for social entrepreneurs and policymakers seeking to enhance the effectiveness and impact of social enterprises.